Harmony in Interfaith Marriage: A Phenomenological Perspective of Alfred Schutz in Bandungan District, Semarang Regency, Central Java - Muhammad Ulinnuha (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2024)
Problem statement: The main problem in this study is that interfaith marriage lies in the tension between individual freedom in choosing a life partner and the legal restrictions and religious norm that regulate the validity and sosial implications of the marriage. Objective: This study aims to capture, understand, and elucidate the meaning behind the phenomenon occurring within families practising interfaith marriage, wherein harmonious and tolerant relationships are established both within the family unit and in the broader community. Methods: This article employs a qualitative research methodology, specifically field research utilising a phenomenological approach. Data collection techniques encompass observation, in-depth interviews, and documentation. Results: The findings indicate that interfaith marriages in Dusun Kedungwangan demonstrate harmony both internally and externally. Internally, harmony is evidenced through communication patterns, educational dynamics, economic balance, and a low incidence of family-related issues. Externally, harmony is reflected in the establishment of harmonious interreligious social relationships within the community. The analysis, guided by Alfred Schutz’s phenomenological theory, identifies two key aspects in uncovering the meaning of social phenomena in the daily life of Dusun Kedungwangan: "Because of Motive," which reveals a conscious awareness of the significance of religious harmony, a fear of social exclusion, and a tendency to adhere to established communal activities; and "In Order To Motive," which underscores a desire to implement the values of Pancasila within society, to gain acceptance and recognition as an integral part of the community, and to preserve existing communal traditions. Conclusion: Based on the analysis of phenomenological theory, the conclusion of this study shows that the meaning of harmony is formed through subjective and intersubjective meaning of couples in living life together despite different beliefs that from social reality in internal relationships and community relations.